1983
DOI: 10.1271/bbb1961.47.693
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical changes in secondary metabolites in wounded and deteriorated cassava roots.

Abstract: Bluish fluorescent and phenolic components were produced in cassava roots in response to cutinjury, and in relation to physiological deterioration and microbial deterioration. The former proved to consist of five coumarin components, the main three of whichwere scopoletin, scopolin and esculin, and the other two were scopoletin-and esculetin-containing conjugates. A main component of the latter was (+)-catechin. Some enzymes pertaining to the production of the secondary metabolites such as acid invertase, phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 0 publications
4
25
0
Order By: Relevance
“…2-Oxoglutarate-dependent dioxygenase, which was recently identified as a pivotal enzyme converting feruoyl-CoA into 69-hydroxyferuoyl-CoA during scopoletin synthesis (Kai et al, 2008), was upregulated during PPD progression only 12 h after harvest. PAL, which initiates phenylpropanoid synthesis, also had increased activity during PPD (Tanaka et al, 1983). We found that both PAL1 and PAL2 abundances were regulated, with up to an 8-fold increase at 24 h after harvest (Supplemental Figure 9).…”
Section: Phenylpropanoid Biosynthesismentioning
confidence: 76%
See 2 more Smart Citations
“…2-Oxoglutarate-dependent dioxygenase, which was recently identified as a pivotal enzyme converting feruoyl-CoA into 69-hydroxyferuoyl-CoA during scopoletin synthesis (Kai et al, 2008), was upregulated during PPD progression only 12 h after harvest. PAL, which initiates phenylpropanoid synthesis, also had increased activity during PPD (Tanaka et al, 1983). We found that both PAL1 and PAL2 abundances were regulated, with up to an 8-fold increase at 24 h after harvest (Supplemental Figure 9).…”
Section: Phenylpropanoid Biosynthesismentioning
confidence: 76%
“…The coumarin scopoletin accumulates to high levels during PPD progression (Tanaka et al, 1983;Wheatley and Schwabe, 1985;Buschmann et al, 2000b;Bayoumi et al, 2010). Enzymes involved in the final steps of scopoletin biosynthesis were significantly upregulated 6 h after harvest (Supplemental Figure 8), including 4-coumarate-CoA ligase and caffeoyl-CoA O-methyltransferase enzymes, which convert 4-coumarate into coumaroyl-CoA and caffeoyl-CoA into feruoylCoA, respectively.…”
Section: Phenylpropanoid Biosynthesismentioning
confidence: 99%
See 1 more Smart Citation
“…The main constituents induced were identified as umbelliferone (12) and scopoletin (13), and the minor ones esculetin and the two ß-D-glucosides such as scopolin and skimminn (Uritani and Hoshiya, 1953;Minamikawa et al, 1962;Tanaka et al, 1983;Minamikawa et al, 1964). In addition, several authors have been reported that scoparone (6,7-dimethoxycoumarin) (14) is the main phytoalexin involved in induced defense mechanism of citrus against pathogens such as Phytophthora parasitica (Afek, et al, 1986), Guignardia citricarpa (De Lange et al, 1976), Penicillium digitatum (Kim et al, 1992) and Diaporthe citri (Arimoto et al, 1986).…”
Section: In Response To Infection For Some Fungi Such Asmentioning
confidence: 99%
“…It is characterized by a blue-black discoloration of the xylem vessels known as "vascular streaking" The onset of PPD is associated with an increase in respiration (Uritani, 1998;Hirose, 1984), changes in lipid composition (Lalaguna and Agudo, 1989), synthesis of ethylene (Hirose, 1984). accumulation of secondary metabolites from the phenylpropanoid pathway, and increases in many enzyme activities, including PAL and chalcone synthase, glucanase, chitinase, proteinase inhibitors, HRGPs, invertase, catalase, dehydrogenase, peroxidase, and polyphenol oxidase (Rickard, 1981;Tanaka et al, 1983). Wounding of cassava roots enhances respiration rates within the first day, which is followed by primary physiological deterioration (Uritani, 1998;Uritani and Reyes, 1984).…”
Section: Post Harvest Physiological Deteriorationmentioning
confidence: 99%